226k views
1 vote
Simplify the following expression using the properties of exponents. The final form of the expressionswith variables should contain only positive exponents. Assume that all variables represent nonzeronumbers.- &x y-22x3y3AnswerKeypadKeyboard Shortcuts

Simplify the following expression using the properties of exponents. The final form-example-1
User Jhorra
by
5.6k points

1 Answer

0 votes

The given expression is,


(-8x^5y^(-2))/(2x^3y^3)

Factor out the number:


\begin{gathered} 8=2\cdot\: 4 \\ =(-2\cdot\:4x^5y^(-2))/(2x^3y^3) \end{gathered}

Cancel out the common factor: 2


=(-4x^5y^(-2))/(x^3y^3)

Simplify the above


(x^5)/(x^3)=x^2

Therefore,


=(-4x^2y^(-2))/(y^3)

Simplify


(y^(-2))/(y^3)=(1)/(y^5)
=(-4x^2)/(y^5)

Apply the fraction rule


(-a)/(b)=-(a)/(b)
=-(4x^2)/(y^5)

Hence, the answer is


-(4x^2)/(y^5)

User Josias Iquabius
by
5.6k points